Off the charts: A comparative analysis of data visualisations in online science news from South Africa and the USA - Marnell Kirsten; Marina Joubert; Ionica Smeets; Winnifred Wijnker (PLoS ONE, 2025)
Terms like ‘big data’, ‘data science’, and ‘data visualisation’ have become buzzwords in recent years and are increasingly intertwined with journalism. Data visualisation may further blur the lines between science communication and graphic design. Our study is situated in these overlaps to compare the design of data visualisations in science news stories across four online news media platforms in South Africa and the United States. Our study contributes to an understanding of how well-considered data visualisations are tools for effective storytelling, and offers practical recommendations for using data visualisation in science communication efforts.